An Innovative Phonetic Mapping of English Vowels and Consonants among EFL Learners - Lubis, Yani; Sinulingga, Elwan Rhidonta; Ritonga, Maimunah Apriani; Arista, Milda Wahyu (MUDABBIR Journal Research and Education Studies, 2025)
This study explores the application of a phonetic mapping model designed to improve the pronunciation of English vowels and consonants among EFL learners. Recognizing that many students struggle with phonemes absent in their native language, the research investigates whether visual and articulatory-based phoneme mapping can enhance learners’ phonological awareness and production accuracy. Using a descriptive classroom-based method, 30 intermediate-level EFL students were divided into control and experimental groups. The experimental group was taught using a phonetic mapping strategy that organizes sounds by articulatory features such as voicing, place, and manner of articulation. Data were collected through pre- and post-tests, learner recordings, and qualitative feedback. The results showed a significant improvement in pronunciation accuracy in the experimental group, with a 28.5% increase compared to 10.2% in the control group. Learners also reported increased confidence and better understanding of English sound systems. These findings suggest that phonetic mapping is an effective tool for improving pronunciation and fostering phonological awareness among EFL learners